Birds Species on Vertical Stratification of Mangrove Vegetation Nusa Lembongan, Bali Indonesia - Ginantra, I Ketut; Muksin, I Ketut; Joni, Martin (Journal of Tropical Biodiversity and Biotechnology, 2023)
This study aims to determine the use of vertical stratification of mangrove vegetation by bird species in the mangrove ecosystem of Nusa Lembongan. The study was conducted at seven mangrove ecosystem sites, in April-July 2021. Observation of the number of birds in each vegetation strata was carried out using the point count method. The association of the use of vegetation strata by bird species was carried out by Detrended correspondence analysis (DCA) statistical test. The results showed that total of 32 species are found in the mangrove ecosystem of Nusa Lembongan which belong to 26 families. There is a strong association between bird species and the vertical strata of vegetation. The species of birds associated with pure mangrove vegetation are; strata I, namely Amaurornis phoenicurus (Pennant,1769), Ardea purpurea Linnaeus, 1766, Sterna bergii M.H.K.Lichtenstein, 1823, Passer domesticus (Linnaeus, 1758), and Pycnonotus aurigaster (Vieillot, 1818); strata II are Todiramphus chloris (Boddaert, 1783), Todirhamphus sanctus (Vigors and Horsfield, 1827), Alcedo coerulescens Vieillot, 1818 and Butorides striata (Linnaeus, 1758); strata III are Hypothymis azurea (Boddaert, 1783), Lanius schach Linnaeus, 1758, Merops philippinus Linnaeus, 1767, Nectarinia jugularis Linnaeus, 1766 and Gerygone sulphurea Wallace, 1864; strata IV are Collocalia linchi Horsfield & F.Moore,1854, Oriolus chinensis Linnaeus, 1766, Hirundo tahitica Gmelin,1789 and Pycnonotus goiaver (Scopoli, 1786). The bird species associated with mixed mangrove and dryland vegetation are strata I, namely species Turnix suscitator (J.F.Gmelin, 1789), Acridotheres javanicus Cabanis, 1851, Anthreptes malacensis (Scopoli, 1786), Passer domesticus (Linnaeus,1758), Pycnonotus aurigaster (Vieillot, 1818), Spilopelia chinensis (Scopoli, 1786) and Geopelia striata (Linnaeus, 1766); strata II, namely Alcedo coerulescens Vieillot, 1818, Zosterops chloris Bonaparte, 1850, Todirhamphus sanctus (Vigors and Horsfield,1827) and Todiramphus chloris (Boddaert, 1783); strata III, namely Anthreptes malacensis (Scopoli,1786), Cacomantis merulinus (Scopoli,1786), Hypothymis azurea (Boddaert,1783), Copsychus saularis (Linnaeus,1758), Nectarinia jugularis Linnaeus, 1766, Gerygone sulphurea Wallace, 1864 and Merops philippinus Linnaeus,1767; strata IV, namely Collocalia linchi Horsfield & F.Moore,1854, Hirundo tahitica Gmelin,1789 and Corvus sp. Factors influencing strata preference by birds are resources, both food and space, as well as the bioecological characteristics of the birds themselves.